Breast Cancer And Breast Cancer Screening Use—Beliefs and Behaviours in a Nationwide Study in Malaysia - Min Min Tan; Aminatul Saadiah Abdul Jamil; Roshidi Ismail; Michael Donnelly; Tin Tin Su (BioMed Central Ltd, 2024)
Indexed by WOS/Scopus/ERA